Development and validation of Indonesian youth career identity scale: the Rasch analysis - Agungbudiprabowo, Agungbudiprabowo; Purwanta, Edi; Wangid, Muhammad Nur (Institute of Advanced Engineering and Science, 2025)
Career identity is one of the most important psychosocial developmental tasks for adolescents. The development of career identity in adolescence will prevent humans from experiencing identity confusion which will have an impact on further developmental tasks. This research answers the need for this measurement tool by developing and validating a career identity measurement tool called the Indonesian youth career identity scale (IYCIS). This instrument consists of 55 items in two aspects: career exploration and commitment. This study uses Rasch analysis to test the validity of the IYCIS construct. The construct validity test involved 200 high school students in Yogyakarta, Indonesia. Data analysis using Winstep software provides information about the quality of respondents and instruments, items that are easy and difficult for respondents to agree on, items that are made to order, and unidimensional. The results of applying the Rasch analysis show that IYCIS is good, precise, and has an item fit with the model. IYCIS is a reliable and valid measurement tool for accurately measuring the level of student career identity. This study discusses the implications and recommendations for further research on the implementation of guidance and counseling that contains career identity as a follow-up to IYCIS performance.